Ripsters Live at KCPR, May 25, 1985 - The Ripsters::::::::: (1985)
The Ripsters live at KCPR on May 25, 1985. Their performances include covers of popular songs [00:00:09] opening music [00:00:32] "Let's Get Together" (Eddie Cochran) [00:04:26] "I Saw Her Standing There" (the Beatles) [00:07:39] "Mean Woman Blues" (Roy Orbison) [00:10:20] "Sea Cruise" (Shakin' Stevens) [00:13:00] song name unknown, possibly "I'm Stepping Out Back" [00:16:45] song name unknown [00:20:37] song name unknown [00:23:00] band chatting amongst themselves and long silence [00:26:08] "Blue Jean Bop" (Gene Vincent) [00:29:15] song name unknown [00:33:09] "Red Rose" (the Blasters) [00:36:05] song name unknown, possibly "Line of Fire" [00:39:17] song name unknown possibly "Rockin' Baby" [00:42:07] "Somethin' Else" (Eddie Cochran) [00:45:30] "All By Myself" (Johnny Burnette)